Hydroisomerization of n-Heptane over HPMo-Ni/Ce-MCM-48 Catalysts - Suo, Yanhua; Chen, Gang; Wang, Yingjun; Zhang, Wei; Li, Lili; Zu, Xinyue (Asian Journal of Chemistry, 2014)
Ce-MCM-48 mesoporous material was prepared by hydrothermal method and used as a support to prepare HPMo-Ni/Ce-MCM-48 catalysts by impregnation process. The crystal structure of catalysts was determined by X-ray powder diffraction, Brunauer-Emmett-Teller methods and FI-IR and SEM. The influences of heteropoly acid loading on catalysts for n-heptane isomerization were studied. The optimum catalyst for n-heptane isomerization was HPMo-Ni/Ce-MCM-48 catalysts with 20 % loading of HPMo. The conversion of n-heptane and the isoheptane selectivity reached to 18.5 and 73.5 %, respectively (reduction temperature: 673 K (for 6 h); reaction conditions: 573 K (for 24 h), weight hourly space velocity = 3.52 h-1, flow rate of H2 = 50 mL/min).